Pengaruh Kepatuhan SOP terhadap Kinerja Ground Handling dalam Pengoperasian GSE di Bandar Udara Sam Ratulangi Manado - Juarni Laurensi Bungkaes; Aditya Dewantari (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Airports serve as a central hub for air transportation, requiring precise coordination and operations, including ground handling services. One key element is the Ground Support Equipment (GSE) personnel, who are responsible for aircraft support equipment. They must adhere to Standard Operating Procedures (SOPs) to ensure performance meets safety and efficiency standards. However, challenges such as timeliness, procedural discrepancies, and inconsistencies in SOP implementation remain. This study used a quantitative approach with correlational analysis and simple linear regression. The sample consisted of 30 GSE personnel selected through total sampling, and data were collected through a questionnaire that had been tested for validity and reliability. This method aimed to identify the effect of SOP compliance. The results showed that SOP compliance had a positive and significant impact on GSE officer performance at Sam Ratulangi Airport in Manado. The regression coefficient of 0.632 indicates a positive relationship, with a significance value of 0.002 indicating statistical significance. The coefficient of determination (R Square) value of 0.241 indicates that 24.1% of the variation in officer performance can be explained by compliance with SOPs, which indicates that increased compliance contributes positively to their performance.